Sleep quality and associated factors among undergraduate medical students in Delhi - Ahlawat, Pooja; Dwivedi, Archana; Dwivedi, Nidhi; Mahaur, Gunjan; Mahaur, Mridul; Singh, Kamaljeet; Jain, Akshita; Sharma, Soumit (International Journal Of Community Medicine And Public Health, 2024)
Background: Sleep disturbances are common among medical students worldwide and affects their health and academic performance. The objective of this study was to assess the quality of sleep in undergraduate medical students of Delhi. Methods: A cross-sectional study was conducted among 234 undergraduate students from medical college in New Delhi. A pre-designed, pre-tested questionnaire was used to collect socio-demographic and life style details and Pittsburgh Sleep Quality Index (PSQI) was used to study the quality of sleep. Data was analyzed by SPSS software version 25.0 and for qualitative data analysis chi-square test was used. Results: Mean age of study subjects was 21.99±1.74 years and males (67.5%) were more as compared to (32.5%) females. Most of the participants 47.4% were in first and second year, 35.5% were from third and final year and 17.1% were interns. Out of 234 participants, only 44% of study participants has good quality of sleep. Most of study participants (56%) were suffering from poor sleep quality. Batch of MBBS, relationship status, BMI and dietary habits of participants were found to be significant predictors of quality of sleep. Conclusions: This study shows that 56% of study participants were suffering from poor quality of sleep. Professionals and medical students who suffer from poor sleep quality have a higher risk of misjudgements, substance abuse, accidents, burnout, anxiety, and depression. So, there is a need to improve knowledge regarding importance of good sleep quality among medical students.